A technique for the fabrication of a more retentive nasal prosthesis - Gelareh Asadi; Ali Mirfazaelian; Amir A Mangoli (Wolters Kluwer Medknow Publications, 2009)
Retention is one of the most important considerations in fabricating a successful facial prosthesis. This article presents a technique using two acrylic resin extensions to provide more retention for a nasal prosthesis.